Investigation of The Impact of Parents' Occupation on The Academic Grades of High School Students - Roshita, Puput; Roihan Achwan; Ratna Setianingsih; Pradita Wulandari (International Journal of Education and Teaching Zone, 2023)
This study analyzes student learning outcomes in terms of the parents of SMA Adhyaksa 1 Jambi City. This type of research is quantitative. The subjects of this study were class XII students of SMA Adhyaksa 1 Jambi City. As for the population, there are 192 students in class XII, with six classes; there are three classes for science and three for social sciences. In the science class, there are 29 students and 67 girls; Meanwhile, there are 50 students and 46 girls in the social studies class. The sample that filled out the Google form was 64 students from 2 science and social studies classes, the technique used was purposive sampling. The data collection method uses the Google form to compare students' academic grades with their parent's work. Parents' occupations were used as the object of study, namely Laborers, Civil Servants, Pensioners and Traders; From the research results, it was found that there were 17 students whose parents worked as labourers with a high academic score percentage of 35% and a low academic score of 65%. Whereas for students whose parents are civil servants, there are 15 students with a high percentage of 60% and 40% with low academic scores. Meanwhile, students whose parents are retired have a high academic rating of 62% and a low academic rating of 38%. And students whose parents work as traders, 19 students with a high percentage of 47% and 53% with low academic grades.